2017
DOI: 10.1038/s41598-017-18419-2
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Eye Disease and Participation in Cognitive Activities

Abstract: Studies have found a benefit to living a cognitively active life in older age. Our goal was to quantify participation in cognitively stimulating activities in adults with and without age-related eye disease. We conducted a cross-sectional hospital-based study in Montreal, Canada of older adults (n = 303) having either age-related macular degeneration (AMD) (n = 96), glaucoma (n = 93), or normal vision (n = 114). To be eligible, the AMD group had to have bilateral late stage AMD with a better eye visual acuity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Having a longer interval between assessment of visual acuity and diagnosis of dementia and excluding those who developed dementia shortly after baseline might help minimize the possibility of reverse causation. Third, people with poor vision might experience more difficulties in accessing services for their health problems and in participating in physical, intellectual, and social activities ( 22 ). Whether poor visual acuity increases the risk of dementia independent of these health conditions and behaviors, which themselves have already been shown to be associated with dementia, requires further investigation.…”
mentioning
confidence: 99%
“…Having a longer interval between assessment of visual acuity and diagnosis of dementia and excluding those who developed dementia shortly after baseline might help minimize the possibility of reverse causation. Third, people with poor vision might experience more difficulties in accessing services for their health problems and in participating in physical, intellectual, and social activities ( 22 ). Whether poor visual acuity increases the risk of dementia independent of these health conditions and behaviors, which themselves have already been shown to be associated with dementia, requires further investigation.…”
mentioning
confidence: 99%
“…Performing fewer activities in older age can increase the risk of Alzheimer's disease or cognitive impairment, 17,18 and the loss of vision late in life may lead to a less active lifestyle. 19 Besides activity level, other potential intervening variables, also called mediators, could include life space and depressive symptoms. Life space, a measure of the spatial extent of a person over the previous month, 20 has been found to be associated with both eye disease 21 and cognitive function, 22 as have depressive symptoms.…”
mentioning
confidence: 99%
“…43,44 We previously reported that people with moderate and severe glaucoma performed fewer activities like reading, playing games, exercising, and socializing than people with normal vision. 45 Previous studies have shown glaucoma to be related to worse scores on the verbal digit forward and backward tests and the logical memory test, 17 the MMSE-Blind, 16 and with increased Alzheimer's disease. 46 Other studies have not shown associations between glaucoma and Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 98%